Biological characterization of novel nitroimidazole‐peptide conjugates in vitro and in vivo. (23rd March 2017) - Bergmann, Ralf; Splith, Katrin; Pietzsch, Jens; Bachmann, Michael; Neundorf, Ines
Abstract : Recently, we reported on the design of a multimodal peptide conjugate useful as delivery platform for targeting hypoxic cells. A nitroimidazole (2‐(2‐nitroimidazol‐1‐yl)acetic acid, NIA) moiety, which is selectively entrapped in hypoxic cells, was coupled to a cell‐penetrating peptide serving as the transporter. Furthermore, attachment of a bifunctional linker allowed the introduction of a diagnostic or therapeutic radiometal. However, although selective tumor accumulation could be detected in vivo, a fast renal clearance of the compound was observed. The present study aims to improve the system by using the more proteolytically stable all‐d version of the peptide carrier (DsC18), by attaching two NIA moieties instead of one (DsC18(NIA)2 ) to enhance the tumor uptake, and by incorporating the bifunctional chelator NODAGA instead of DOTA (NODAGA‐DsC18(NIA)2 ) to optimize labeling chemistry. First, we characterized in vitro the novel all‐d peptide compared with its parentl ‐version. Then, in order to investigate and compare the pharmacological profiles of the peptides, these were radiolabeled with 64 Cu II and 68 Ga III, and the biodistribution and kinetics were evaluated in vivo . Our results show the versatility of thed ‐peptide as cell‐penetrating peptide and transporter. However, attaching two NIA groups modified the system in such a way that no selective tumor uptake could be observed compared with the peptide without NIA moieties. Still, this work highlights new pharmacokinetic data on the biodistribution of such compounds in vivo . Copyright © 2017 European Peptide Society and John Wiley & Sons, Ltd. Abstract : Novel modified nitroimidazole‐peptide conjugates are presented. For a detailed characterization, the conjugates were labeled either with a fluorophore or via the bifunctional chelator NODAGA with 64 Cu II or 68 Ga III, respectively.